Healing architecture: daylighting design in hospital environments in Malaysia - Aripin, Srazali (AWG Publishing, Toronto, Canada, 2010)
The climate in Malaysia is generally hot and humid throughout the year, with abundant daylight. Daylight is required as part of a healthy environment. This paper highlights the role and importance of daylight in the design of hospitals in Malaysia. Focusing on case studies of existing conditions in public hospital buildings in Malaysia, the author critically examines the design and implementation of lighting and the relationship of lighting to other environmental factors. Previous studies relating to physical environmental factors in hospital buildings that influence health outcomes are also critically reviewed. © 2010 by AWG Publishing, Toronto, Canada.